DETECTION OF MUTATIONS RELATED TO HEREDITARY CANCER IN RELATIVES OF BREAST CANCER PATIENTS - G. A. Paul; N. A. Matyash; E. E. Pisareva; M. S. Anisimenko; A. E. Kozyakov; S. P. Kovalenko (Сибирский онкологический журнал)
The BRCA1 5382insC and CHEK2 1100 delC mutations were analyzed in 3850 of non-selected breast cancer patients residing in Novosibirsk region, Russia. One hundred seventy probands, BRCA1 5382insC or CHEK2 1100delC mutation carriers, were found. The study demonstrated that more than 80 % of probands informed relatives about their hereditary or familial cancer risk. Fifty-nine BRCA1 5382insC and CHEK2 1100 delC mutation carriers were found among 144 proband’s relatives. Mutation carriers or their relatives were interviewed two years after starting the project. At least 18 % of the mutation carriers reported primary tumor or recurrence of the tumor 2 years after starting the project.